Preliminary ruling of the ECJ and the Akcenta case - Katarína Kalesná (DANUBE: Law, Economics and Social Issues Review, 2018)
The article analyses the significance of the ECJ preliminary ruling on competition law. Starting with the general characteristic of the preliminary ruling of the Court of Justice, its legal regulation in TFEU and its effects, it focuses on the concrete judgement of the Court (Tenth Chamber) of 7 February 2013 in Case C-68/12 at the request of the Supreme Court of the Slovak Republic. It explains the preliminary questions and the background of the competition case that was the incentive for them. It describes the quite complicated cartel agreement of the three banks concerned and the impact of the ECJ preliminary ruling on the judgements/decisions of the case.
Keywords: 330; Preliminary Ruling/Questions; Agreement Restricting Competition; Cartel; Procedure; Competition Authority; National Court; European Court of Justice